Nadzór miejski. Próba ujęcia problematyki na podstawie filmu „Raport mniejszości” - Wójcik, Krzysztof (Załącznik Kulturoznawczy, 2023)
In this article, I try to present the problems of modern surveillance, using three perspectives: theoretical, practical and pop-cultural. The first chapter provides a theoretical basis. Through adapting theories of selected philosophers, including Michel Foucault and Giorgio Agamben, I’m trying to create a cognitive frame, constituting the key to understanding the contemporary supervision discourse. In the next part of the work I make a synthetic presentation of the current forms of social control, emphasizing their tendency to encroach on every area of human life. In the third, crucial chapter, I carry out an analysis of the film Minority Report, using the interpretation tools developed in the first chapter. Specifying certain elements of the Steven Spielberg’s film, I interpret the image in the spirit of social supervisiondiscourse. At the same time I try to hghlight the number of threads and the interpretative ambiguity of the film − a thoroughly pop-cultural image, which constitutes a very interesting diagnosis of contemporary reality.